Deep clinical, genetic, and serum biomarker profiling indicates glial and neuronal pathology in primary brain calcification - Schwahn, Janine; Hebestreit, Sophie; Kosche, Olivia; Steinacker, Petra; Sandikci, Vesile; Winzer, Isabel; Hesebeck-Brinckmann, Jasper; Bachhuber, Franziska; Valkadinov, Ivan; Nittka, Stefanie; Mesin, Lukas; Brauner, Max; et al. (Brain communications, 2025)
Primary brain calcification (primary familial brain calcification in inherited cases) is an often-genetic condition characterized by symmetrical brain calcifications and neuropsychiatric symptoms. The calcifications can also occur without overt clinical symptoms. Identifying laboratory biomarkers in primary brain calcification and their association with imaging, genetic, and clinical data will be crucial for a deeper understanding of primary brain calcification causation and progression and the planning of therapeutic trials. The serum biomarkers for neuronal degeneration (phosphorylated tau, neuron-specific enolase, neurofilament light- and heavy chain) and glial activation (glial fibrillary acidic protein, S100 calcium-binding protein B) were measured in 101 probands (41 controls and 60 probands with primary brain calcification). The deep phenotyping protocol of the German Fahr-NET register included neurological and neuropsychological examination, routine laboratory workup, and whole exome sequencing. We also performed and analyzed 45 cranial CT scans using the total calcification score. While mild pallidal calcifications were observed early in young, asymptomatic primary brain calcification mutation carriers, individuals with calcifications extending beyond the pallidum were symptomatic. Individuals with primary brain calcification had elevated serum glial fibrillary acidic protein and neurofilament light chain levels. Serum biomarkers correlated with both the extent of calcifications and the clinical impairment. Elevated parathyroid hormone levels distinguished the primary brain calcification group without identified mutation from both genetic primary brain calcification and control groups. Our results define a practical imaging cut-off indicating the presence of primary brain calcification symptoms. Elevated parathyroid hormone levels in primary brain calcification without identified mutation, but not in primary brain calcification with a monogenic cause, suggest abortive calcium regulation defects as a pathogenic factor specifically for primary brain calcification without identified mutation. Elevated glial fibrillary acidic protein and neurofilament concentrations in individuals with primary brain calcification indicate early, chronic astrocytosis and neuronal impairment, respectively. The significant association of neurofilament light chain with clinical scores and brain imaging results will be relevant for future therapeutic studies.